Novel homozygous mutation of PNLIP gene in congenital pancreatic lipase deficiency: an extended family study - Naglaa M. Kamal; Omar I. Saadah; Shahad S. Alheraiti; Ruwayd Attar; Asmaa D. Alsufyani; Moratda H.F. El-Shabrawi; Laila M. Sherief (SAGE Publishing, 2022)
Introduction: Congenital pancreatic lipase deficiency (MIM 614338) is a rare genetic disorder caused by homozygous mutation in the PNLIP gene. Few cases have been reported worldwide and among them, few cases were genetically confirmed. Patients and methods: A 3-year-old girl presented with abundant greasy diarrhea started at the age of 2 years. Work up of steatorrhea including molecular testing of PNLIP gene in the patient and her family was done. Results: A novel homozygous variant c.1257G > A (p. Trp419Ter) of the PNLIP gene was detected in the patient. Her parents and two siblings were carriers for the same mutation. Pancreatic enzyme therapy was introduced, and a multidisciplinary team was involved with the education for the need for the lifelong use of pancreatic enzymes, and genetic counseling was carried out. There was a great improvement of steatorrhea with pancreatic enzymes treatment. Conclusions: PNLIP deficiency should be suspected in patients with steatorrhea who have low pancreatic lipase and an otherwise normal health and appropriate growth.